2018
DOI: 10.5585/gep.v9i1.589
|View full text |Cite
|
Sign up to set email alerts
|

Pesquisa em Sistemas de Informação no Brasil: 27 Anos sob uma Ótica Internacional

Abstract: Compreendendo que conhecer o passado é importante para planejar o futuro, neste artigo buscamos resgatar a história de sistemas de informação no Brasil, tendo como marco inicial o ano de 1988, quando a área de administração da informação (ADI) surge pela primeira vez de forma independente em um dos principais congressos de administração do Brasil, o EnANPAD. Como marco final, o ano de 2014, que representa a comemoração dos 20 anos da AMCIS (Americas Conference on Information System), evento que é referência na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…Antonio Carlos Maçada, professor at the Federal University of Rio Grande do Sul (UFGRS) and Director of ANPAD (2018-2020) comes in second place (50.0%). In fact, both Edimara Mezzomo Luciano and Antonio Carlos Maçada are among the ten most productive authors according to the ANPAD ADI area (Freitas, Marcolin, Becker & Martens, 2018).…”
Section: Analysis and Discussion Of Part B Results (Open-ended Questions)mentioning
confidence: 99%
See 1 more Smart Citation
“…Antonio Carlos Maçada, professor at the Federal University of Rio Grande do Sul (UFGRS) and Director of ANPAD (2018-2020) comes in second place (50.0%). In fact, both Edimara Mezzomo Luciano and Antonio Carlos Maçada are among the ten most productive authors according to the ANPAD ADI area (Freitas, Marcolin, Becker & Martens, 2018).…”
Section: Analysis and Discussion Of Part B Results (Open-ended Questions)mentioning
confidence: 99%
“…Information technology governance (ITG) is an emerging theme that is expanding in the international academic arena, as pointed out by Khan and Wood (2015); at a national level, the topic is quite stable (Freitas, Marcolin, Becker & Martens, 2018). Incidentally, ITG is always present at the main international and national congresses, with a significant number of research groups involved , as it is signaled as a strategic subject for executives worldwide (Kappelman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Other keywords referring to the theme remain in pre-eminence, such as 'performance', 'value' and 'framework', as well as 'alignment' and 'strategic IT management', which are emerging themes, indicating the direction of current academic research. Freitas et al (2018) identifies that ITG or Strategic and Competitive Use of Information Technology, a classification used in this study, although with some stability and a clear decrease in production in the last period, represents the second largest volume of production in Information Systems within the ANPAD events, the main national event of the Brazilian Administration area.…”
Section: Scientific Capital and Graduate In Brazilmentioning
confidence: 99%
“…In this way, the most frequent words were: 'study' (57), 'cases' (43), 'model' (33), 'companies' (30), 'public' (21), 'practices' (20), 'analyze' (19), 'institution' (19), 'management' (19), 'Brazilian' (18), 'federal' (18), 'process' (18), 'organization' (16), 'sector' (15), 'service' (15), 'application' (12), 'corporate' (12), 'evaluation' (12), 'base' (11), 'strategic' (11), 'teaching' (11), 'alignment' (10), 'implantation' (10), 'relationship' (10), among other verified words, in that order. When the research objects or themes were analyzed, the following terms were identified: 'Government' (26), 'Teaching Institutions' (19), 'Banking / Finance' (7), 'Companies in general' 7, 'Health' 7, 'Industry' (6), 'National enterprises' 5 The ITG theme in government or public administration has been a subject widely studied by researchers, as demonstrated in more detail in a study conducted by Chagas et al (2015).…”
mentioning
confidence: 99%
“…2018-ISSN 1983-3652 DOI: 10.17851/1983 particularmente relacionados à modalidade de ensino a distância (EaD), impõe uma série de desafios no processo de ensino-aprendizagem. O estudo feito pelo Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira (Inep) sobre dados relacionados ao Censo da Educação Superior de 2016 indicou um crescimento do número de estudantes da ordem de 7,2% (INEP, 2016) em comparação com o levantamento anterior, refletindo, assim, uma tendência internacional (FREITAS et al, 2018;SHESHASAAYEE;NAZREEN BEE, 2018).…”
Section: Introductionunclassified